Adaptive Biasing Force Method: Difference between revisions

Jump to navigation Jump to search
no edit summary
No edit summary
No edit summary
Line 61: Line 61:


====Simplified ABF Algorithm====
====Simplified ABF Algorithm====
The simplified ABF algorithm (fmode=1) uses the result of the product rule for derivatives applied on Equation 3:
The simplified ABF algorithm (fmode=1) uses the result of the product rule for derivatives applied on Equation 3 leading into the two distinct contributions into the instanteous collective forces:
   
   
<center><math>\frac {d} {dt} \left( \bold Z^{-1} \frac{d \boldsymbol \xi} {dt} \right) \big|_{(t)} = + \left( \bold Z^{-1}(t) \nabla \boldsymbol \xi (t) \right) \cdot \bold a(t) + \frac{d}{dt} \left( \bold Z^{-1}(t) \nabla \boldsymbol \xi (t)) \right) \cdot \bold v(t) = \bold F_{ICF,pot} + \bold F_{ICF,kin}</math> ... (11)</center>
<center><math>\frac {d} {dt} \left( \bold Z^{-1} \frac{d \boldsymbol \xi} {dt} \right) \big|_{(t)} = + \left( \bold Z^{-1}(t) \nabla \boldsymbol \xi (t) \right) \cdot \bold a(t) + \frac{d}{dt} \left( \bold Z^{-1}(t) \nabla \boldsymbol \xi (t)) \right) \cdot \bold v(t) = \bold F_{ICF,pot}(t) + \bold F_{ICF,kin}(t)</math> ... (9)</center>


The accelerations <math>\bold a(t)</math> are calculated from the velocities to incorporate the effect of SHAKE constraints in [[the leap-frog integration algorithm]]:
The potential contribution <math>\bold F_{ICF,pot}(t)</math> employs the accelerations <math>\bold a(t)</math> calculated back from the velocities. This ensures that effect of SHAKE and other constraints on acceleration is properly counted (see [[Molecular_Dynamics_Algorithms|the leap-frog integration algorithm]] for further details):


<center>\bold a(t) = \frac{\bold v(t+dt/2) - \bold v(t-dt/2)}{dt}<math>
<center><math>\bold a(t) = \frac{\bold v(t+dt/2) - \bold v(t-dt/2)}{dt}</math> ... (10)</center>


The kinetic contribution <math>\bold F_{ICF,kin}(t-dt/2)</math> is calculated from numerical differentiation:


<center><math>\bold F_{ICF,kin}(t-dt/2) = \frac {\bold Z^{-1}(t) \nabla \boldsymbol \xi (t) - \bold Z^{-1}(t-dt) \nabla \boldsymbol \xi (t-dt)}{dt} \bold v(t-dt/2) </math> ... (11)</center>
Finaly, to get <math>\bold F_{ICF,kin}</math> at the same time as <math>\bold F_{ICF,kin}</math>, two values are averaged:
<center><math>\bold F_{ICF,kin}(t) = \frac {\bold F_{ICF,kin}(t+dt/2) + \bold F_{ICF,kin}(t-dt/2) }{2}</math> ... (12)</center>
The algorithm uses a history of values collected in two consecutive time steps. But, the first result is available from the fourth time step to be compatible with the original algorithm.


The accel
The accel

Navigation menu